Analysis of Disability Public Policy in Ecuador: The Adoption of Goals in the Public Agenda and Intersectoral Coordination in Policy Change (2010–2020) - Farinango Salazar, Luis Wladimir (Journal Studies of Public Policy, 2024)
This article analyzes how the adoption of quality of life and participation objectives established a policy change in Ecuador during the 2010-2020 period. The methodological design is based on the analytical framework of public policy design, where the causal mechanism connects a trigger with a result. The methodological process is qualitative, grounded in process tracing. To verify the evidence, the NATO instruments of the State are applied: nodality, authority, treasure, and organization (Hood, 1987). The findings reveal that the adoption of quality of life and participation objectives led to the formulation of laws, codes, and statutes, which, through State mechanisms, were linked to an intersectoral coordination process. This enabled policy coordination across sectors, involving state and non-state actors as well as civil society, fostering policy change.